Estudio del comportamiento de biofertilizantes elaborados a base de estiércoles y aplicados en tres dosis diferentes en el cultivo de pepino (Cucumis sativus), en época lluviosa en la zona de Mocache. - Lagua Intriago, Jonathan Marcelo (2015)
The overall objective of the research was to evaluate the behavior of biofertilizers elaborated with manure, cattle, broilers and pork, in three high doses 120, medium 80 and low 40 liters per hectare in the cultivation of cucumber ( Cucumis sativus) Mocache area in the Province of the Rivers it held in the experimental farm's Maria Quevedo State Technical University that is located at kilometer 7.1 / 2 via Quevedo - El Empalme, Rivers Province. The geographical location is 01 06 "South altitude and 79 29 'West longitude, located at a height of 120 meters above sea level. The agro-climatic characteristics of the area is wet tropical, annual average temperature of 24.8 ° C, annual rainfall of 2252.5 mm, relative humidity of 84% and 894.0 hours of Heliophany annual average. The soil is loam - clay, irregular topography and drainage with a pH of 5.8.